Preliminary screen for mild cognitive impairment among elderly at old folks home - Abd. Wahid, Nur Haidzat (2012)
Mild Cognitive Impairment (MCI) is a condition characterized by significant decline in cognitive functioning in the absence of dementia. The main symptoms of having MCI are that it affects one’s memory and may result changes in a person’s daily functioning. The aim of this study was to screen for the presence of MCI and depressive symptoms of the elderly at Yayasan Al-Jenderami old folks’ home along with describing the demographic data, screening and neurocognitive assessment results. 33 female elderly were chosen as respondents with age ranging between 56 and 76. There were three illiterate elderly and therefore, they voluntarily withdrew due to difficulty in comprehending the test instructions. The sample was chosen through purposive sampling. In order to achieve the objectives of this study, screening tests administered were Mini-Mental State Examination (MMSE) and Clock Drawing Test (CDT) whereas the neuropsychological tests were Rey Auditory Verbal Learning Test (RAVLT) and Comprehensive Trail Making Test (CTMT). Also, Geriatric Depression Scale (GDS) was used to identify the presence of depressive symptoms. The results of the overall tests as discovered by the neurocognitive profile and interview, showed that 90% of the elderly respondents were found to fall in the category of having signs of MCI. Initially, 18 elderly were reported to have presence of MCI but nine more were categorized as having MCI after further assessment using the neuropsychological tests, RAVLT and CTMT. Thus, future studies may include a more complex set of tests to gain a more insightful look into the development and prevalence of MCI.